Tratamento da humidade ascensional no património histórico - De Freitas, V. P.; Guimarães, A. S. (Revista ALCONPAT, 2014)
Rising damp linked with the salts is a factor in old buildings walls degradation, which requiresknowledge of its higrothermal behavior, as well as the treatment techniques and itseffectiveness knowledge. The rising damp treatment is very complex and many of thetechniques to solve the problem do not show the desirable effectiveness. The Building PhysicsLaboratory of the Faculty of Engineering of the University of Porto has developed numericaland experimental research that allowed the validation of a technology based on the wall basehygroregulated ventilation to treat rising damp, patent the system-HUMIVENT.This paper aims to describe the pathologies associated to rising damp; the advantages anddisadvantages of the most common available technologies for its treatment; characterize therising damp treatment system-HUMIVENT, their implementation in Portuguese buildings andthe analysis of the obtained results.Keywords: rising damp, historical building, hygroregulated system